PENGARUH PENGGUNAAN PEMBELAJARAN DARING TERHADAP HASIL BELAJAR SISWA - Pratiwi, Novi Niken; Puspasari, Durinda (JAMP : Jurnal Administrasi dan Manajemen Pendidikan, 2021)
This study aims to analyze the effect of using online learning on student learning outcomes in the subjects of General Administration class X OTKP SMK Muhammadiyah 7 Gondanglegi Malang. This research is quantitative. The data collection technique used is a questionnaire. The population in this study was 113 students of class X OTKP at SMK Muhammadiyah 7 Gondanglegi Malang. The sample in this study was 88 students using proportional random sampling. The test of the instrument consisted of a validity test and a reliability test. Data analysis techniques include: 1) classical assumption test consisting of normality test and heteroscedasticity test; 2) hypothesis testing using simple linear regression. The results no significant effect online learning on student learning outcomes in the subjects of General Administration class X OTKP SMK Muhammadiyah 7 Gondanglegi Malang.